PEMBELAJARAN INOVATIF MONOPOLI AKSARA BALI DALAM MENINGKATKAN PEMAHAMAN MEMBACA AKSARA BALI - Ida Ayu Made Yulia Rastuti; Ida Ayu Putu Purnami; I Wayan Gede Wisnu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to (1) describe the learning research conducted by teachers using Monopoly Bali learning media to improve the understanding of reading Balinese script of class VII students of SMP N 3 Abiansemal. (2) Monopoly Balinese language learning media can be used by class VII students of SMP N 3 Abiansemal to learn and read Balinese script. (3) Data on students who use monopoly Balinese script learning media to improve the understanding of reading Balinese script of class VII students of SMP N 3 Abiansemal. The data of this study were collected using a qualitative descriptive approach through data collection using practical tests and questionnaires. The subjects of this study were class VII students of SMP N 3 Abiansemal. The results of this study are 1) The level of understanding when reading Balinese script using monopoly Balinese script learning media. 2) Monopoly Balinese script learning media can be used by class VII students of SMP N 3 Abiansemal to understand and read Balinese script. 3) Data on class VII students of SMP N 3 Abiansemal in the application of monopoly Balinese learning media for understanding and reading Balinese script. This research has implications that can be used for the development of the teaching and learning process.